Comparative effectiveness of three versions of a stepped care model for insomnia differing in the amount of therapist support in internet-delivered treatment: study protocol for a pragmatic cluster randomised controlled trial (GET Sleep). Issue 8 (3rd August 2022) - Spiegelhalder, Kai; Baumeister, Harald; Al-Kamaly, Abdulwahab; Bader, Martina; Bauereiss, Natalie; Benz, Fee; Braun, Lina; Buntrock, Claudia; Burkhardt, Maike; Cuijpers, Pim; Domschke, Katharina; Dülsen, Patrick; et al.
Abstract : Introduction: It is unclear how internet-delivered cognitive-behavioural therapy for insomnia (CBT-I) can be integrated into healthcare systems, and little is known about the optimal level of therapist guidance. The aim of this study is to investigate three different versions of a stepped care model for insomnia (IG1, IG2, IG3) versus treatment as usual (TAU). IG1, IG2 and IG3 rely on treatment by general practitioners (GPs) in the entry level and differ in the amount of guidance by e-coaches in internet-delivered CBT-I. Methods and analysis: In this randomised controlled trial, 4268 patients meeting International Classification of Diseases, Tenth Revision (ICD-10) criteria for insomnia will be recruited. The study will use cluster randomisation of GPs with an allocation ratio of 3:3:3:1 (IG1, IG2, IG3, TAU). In step 1 of the stepped care model, GPs will deliver psychoeducational treatment; in step 2, an internet-delivered CBT-I programme will be used; in step 3, GPs will refer patients to specialised treatment. Outcomes will be collected at baseline, and 4 weeks, 12 weeks and 6 months after baseline assessment. The primary outcome is insomnia severity at 6 months. An economic evaluation will be conducted and qualitative interviews will be used to explore barriers and facilitators of the stepped care model. Ethics and dissemination: The study protocol was approved by the Ethics Committee of the Medical Centre—University of Freiburg. The results of the study will be published irrespective of the outcome. Trial registration number: DRKS00021503.